DEVELOPMENT AND EVALUATION OF NUTRILADDU FOR COMBATING ANAEMIA AND UNDERWEIGHT - MALARVIZHI. V (The Journal of Research ANGRAU, 2025)
This study conducted in 2023 aimed to develop iron and calorie rich nutritious recipe from inexpensive and indigenous ingredients, to be used as food supplement to prevent anaemia and enhance weight among undernourished and anaemic individuals.Iron rich ingredients such as Bajra, Amaranth seeds, Rice flakes, Black gram, Roasted Bengal gram, Groundnuts Sesame, Garden cress seeds, Cauliflower leaves powder, Amla powder were used to formulate nutrimix at three different proportions as variations V1, V2 and V3 along with Jaggery and Ghee to prepare Nutriladdu. Organoleptic evaluation was done by a panel of 30 semi trained members using 9 point hedonic scale to assess the sensory attributes of the prepared laddus. Nutritional analysis was conducted to estimate energy, protein, carbohydrate, fat, iron, and beta carotene, along with a microbiological analysis to assess shelf life. The results showed that the laddu prepared with nutrimix V1 was selected as food supplement, due to its highest average sensory score as determined by one-way ANOVA compared to the other compositions. The nutritional analysis indicated that the Nutriladdu (V1) per 100g contains 412 kcal, 12.93g of protein, 47.78g of carbohydrates, 18.36g of fat, 7.324mg of iron, 65.93mg of calcium, and 30.07µg (8.42 IU) of vitamin A. Shelf-life analysis showed acceptability for up to 15 days of storage at room temperature. The findings indicate a potential enhancement of nutrient content in recipes by integrating cauliflower leaves, garden cress seeds, and amla at a 10 percent level, without adversely affecting sensory quality. Fortifying the menu with nutriladdu as a snack would serve as an effective food based strategy to prevent or ameliorate anemia and promote weight gain among undernourished individuals